178k views
3 votes
What is (2x+3)(x- 8)= 3+2(x- 5)(x + 5)

User Yudelka
by
5.4k points

2 Answers

4 votes

Answer:

x^3= 11/-7

Explanation:

(2x+3)(x- 8)= 3+2(x- 5)(x + 5)=

2x^2-16x+3x-24= 3+2x-10+x+5

-11x-24= -2+3x

-11x^2 -24 = -2+3x

-11x^2-3x = -2+24

-14x^3 = 22

x^3 = 22/ -14

x^3 = 11/-7

User Krzysztof Wende
by
5.3k points
5 votes

Answer:

- 23/13

Explanation:

first, we do the FOIL multiplication (First, Outer, Inner, Last)

(2x+3)(x- 8)= 3+2(x- 5)(x + 5)

2x(x-8) + 3(x-8) = 3 + 2(x(x+5) - 5(x+5))

2x² - 16x + 3x - 24 = 3 + 2(x² + 5x - 5x -25)

2x² - 16x + 3x - 24 = 3 + 2(x² - 25)

2x² - 16x + 3x - 24 = 3 + 2x² - 50

2x² - 13x - 24 = 3 + 2x² - 50

after that move all component which have x to the left

2x² - 2x² - 13x = 3 - 50 + 24

-13x = 23

x = - 23/13

User Adrian Avram
by
4.8k points